Penambahan daun kelor pada restructured chicken product sebagai sumber antioksidan - Ni’matus Sholihah; Laili Hajidah (Agroindustrial Technology, University of Trunojoyo Madura, 2023)
Moringa leaves are still utilized in a limited number of processed food items. Moringa is mostly used as a vegetable. Moringa leaves contain enzymes that produce disagreeable scents; thus, their utilization requires product innovation. Nuggets are processed meats that are simple to prepare due to their inclusion in frozen foods that can be readily prepared and kept, but the hue is often unappealing. Fortification is one of the processes that involves adding nutrients to a food product so that it has nutritional value. sufficient. The inclusion of antioxidants produced from Moringa leaves in this nugget product provides nutrition. This study aims to determine the effects of increasing the concentration of moringa leaves on the quality of chicken nuggets as well as the interaction between the usage of concentration and treatment of moringa leaves on the quality of chicken nuggets. The research design used was a factorial randomized block design (RAK) with two treatment factors. Factor 1 was added Moringa leaves which consisted of 3 levels (fresh Moringa leaves, dried Moringa leaves, blanching Moringa leaves), and factor 2 was the concentration of Moringa leaves, which consisted of 3 levels (10%, 15%, 20%). The parameters of the tests were water, ash, texture, fat, protein, chlorophyll, and antioxidants. The best treatment was on 20% fresh leaf treatment which had 63.24% water content, 7.33% ash content, 0.36% chlorophyll, 55.66% antioxidant, 6.07% fat, 12.05% protein. Moringa nuggets are a potential outcome of Moringa leaf innovation.